The Influence of Empowerment Leadership on Proactive Behavior of Employees With Goal Orientation as a Mediation Variable at the Women's Empowerment Office, Protection Children and the People of Binjai City - Kherunisa R. Galua; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2024)
A deep understanding of the relationship between empowering leadership styles, goal orientation, and proactive behavior of employees can be key to optimizing organizational performance in addressing sensitive issues related to women, children, and society more effectively. The purpose of this study is to find out and analyze the influence of Empowerment leadership on Proactive Behavior mediated by the Orientation of the purpose at the Office of Women's Empowerment, Child Protection and Community of Binjai City. This research was conducted with a causal associative quantitative approach. The sample used was all employees, with a total of 61 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) show that 1) There is no influence of Empowerment Leadership on proactive behavior. where the T-statistic value is 0.960 < 1.96 and the P-Value value is 0.341 > 0.05. 2) Empowerment Leadership has a positive and significant effect on goal orientation with a T-Statistical value of 2.256 > 1.96 and a P-Value of 0.028 < 0.05 which means that if the leadership Empowerment is improved, then employee goal orientation will increase.3) Empowerment Leadership has a positive and significant effect on goal orientation with a T-Statistical value of 2.256 > 1.96 and a P-Value value of 0.028 < 0.05 which means that if Empowerment leadership is improved, employee goal orientation will increase and 4) Goal orientation is able to mediate the influence between Empowerment Leadership and Proactive Behavior with a T-Statistic value of 2.300 > 1.96 and a P-Value of 0.025 < 0.05. The implication of these findings is that management needs to consider implementing appropriate goal-oriented development strategies, along with empowerment leadership practices, to create a work environment that supports and encourages productive and innovative proactive behaviorsLeadership Empowerment